Effect of Acupressure and Changes in Heart Rate Variability in Dysmenorrhoea - Thirumeni, R. Archana, V. Philominal, Shyamala (Recent Research in Science and Technology, 2011)
Dysmenorrhoea is a common distressing disorder in women that manifests during menstrual phase especially in young females. The subjects suffering from pain during mensuration are considered to be dysmenorrhoeic. In our studies we have used heart rate variability (HRV) as a sensitive marker of autonomic activity. Autonomic nervous system activity was assessed by means of heart-rate variability (HRV) power spectral analysis during supine rest. The purpose of this study was to assess the changes in heart rate variability in dysmenorrhoea by assessing sympathetic activity and parasympathetic activity and to find out the effect of acupressure therapy whether it is beneficial or not in alleviating the symptoms of dysmenorrhoea. HRV and intensity of pain was assessed before and after acupressure therapy in dysmenorrhoea. Pain intensity was graded using Visual analogue scale. We have noted a significant alteration in autonomic function which may be an important component of premenstrual syndrome (PMS). Acupressure therapy has been effective in regulating the autonomic alterations. Acupressure therapy is an ancient Oriental healing method that applies pressure through a blunt probe to specific points on the skin surface which helps to prevent and treat illness. Acupressure therapy has also significantly reduced the dysmenorrhoeic pain as observed from our visual analogue scores. Our study has clearly revealed the beneficial effect acupressure on dysmenorrhea. It is a very simple procedure that can easily be taught to be self practiced by the dsymenorrhoeic females to relieve the pain during mensuration. It will be a simple drugless inexpensive method to relieve the pain without any side effects.